Analysis of Physical Environmental Factors in Zebra Dove (Geopelia striata) Rearing Systems in Chana District, Songkhla Province - Rungrut, Supattra; Boonkaew, Rachada; Phantaweesub, Narumol; Maprasit, Saudee; Madmanang, Romsan (YRU Journal of Science and Technology, 2026)
Zebra Dove (Geopelia striata) farming is an important community economic activity that faces challenges from both internal and external environment factors, particularly physical environment factors. This research aims to analyze the physical environment factors affecting Zebra Dove farming in Chana District, Songkhla Province. The study utilized a quantitative approach, collecting data from five sample farms located in five main zones of Chana District during two seasons: the rainy season and the summer season. Relative humidity, temperature, dust levels, light intensity, and noise level were measured. The findings revealed that the physical environmental conditions for Zebra Dove keeping included a temperature range of 26–30°C, relative humidity of 70–85%, light intensity of approximately 200–1,000 lux, noise levels not exceeding 60 decibels, and dust concentration not exceeding 0.15 milligrams per cubic meter. Farms in Ban Khu and Na Thap demonstrated the most suitable environmental quality, as their conditions were highly consistent with the recommended standards for poultry management in tropical regions, particularly regarding noise levels and dust concentration, which remained low and positively contributed to the welfare of zebra doves. In contrast, farms in Ban Na Tin and Khok Ma required improvements in dust and noise management. The findings suggest three key measures for sustainable Zebra Dove farming: establishing environmental standards, adopting real-time monitoring technology, and ensuring proper farm environment management.